Too Few Tomorrows (Appalachian State University, 2024)
Between the 1940s and 1970s, approxiately three million people left the Appalachian mountains in search of jobs in Midwest urban areas, such as Cincinnati, Chicago, and Detroit. Unfortunately, about a third of these people were forced into a life of long-term underclass dwellers. Struggling with questions of identity, rootlessness, and cultural negation, these people were given the name of “urban Appalachians.” Published in 1987, Too Few Tomorrows addresses some of the pressing questions regarding urban Appalachians and their story of migration to city life.